Impact of ruxolitinib pretreatment on outcomes after allogeneic stem cell transplantation in patients with myelofibrosis. (4th July 2018) - Shahnaz Syed Abd Kadir, Sharifah; Christopeit, Maximilian; Wulf, Gerald; Wagner, Eva; Bornhauser, Martin; Schroeder, Thomas; Crysandt, Martina; Mayer, Karin; Jonas, Julia; Stelljes, Matthias; Badbaran, Anita; Ayuketang Ayuk, Francis; et al.
Abstract: Introduction: Ruxolitinib is the first approved drug for treatment of myelofibrosis, but its impact of outcome after allogeneic stem cell transplantation (ASCT) is unknown. Patients and methods: We reported on 159 myelofibrosis patients (pts) with a median age of 59 years ( r : 28‐74) who received reduced intensity ASCT between 2000 and 2015 in eight German centers from related (n = 23), matched (n = 86) or mismatched (n = 50) unrelated donors. Forty‐six (29%) patients received ruxolitinib at any time point prior to ASCT. The median daily dose of ruxolitinib was 30 mg (range 10‐40 mg) and the median duration of treatment was 4.9 months (range 0.4‐39.1 months). Results: Primary graft failure was seen in 2 pts (4%) in the ruxolitinib and 3 (2%) in the non‐ruxolitinib group. Engraftment and incidence of acute GVHD grade II to IV and III/IV did not differ between groups (37% vs 39% and 19% vs 28%, respectively), nor did the non‐relapse mortality at 2 years (23% vs 23%). A trend for lower risk of relapse was seen in the ruxolitinib group (9% vs 17%, P = .2), resulting in a similar 2 year DFS and OS (68% vs 60% and 73% vs 70%, respectively). No difference in any outcome variable could be seen between ruxolitinib responders and those who failed or lost response to ruxolitinib. Conclusions: These results suggest that ruxolitinib pretreatment in myelofibrosis patient does not negatively influence outcome after allogeneic stem cell transplantation.